The synthesis of [14C]4‐acetylphenylalanine, effect on cell viability, and assessment of protein incorporation in male rat hepatocytes. (30th May 2017) - Maxwell, Brad D.; Ly, Van; Brock, Barry; Dodge, Robert; Tirmenstein, Mark; Calvano, Jacqueline
Abstract : PEGylation is a proven approach to prolonging the duration of action and enhancing biophysical solubility and stability of peptides. 4‐Acetylphenylalanine is a novel amino acid with a ketone side chain that is uniquely reactive in proteins. The ketone functionality can react with an aminooxy functionalized polyethyleneglycol polymer to form a stable oxime adduct of the protein. One concern with using unnatural amino acids, such as 4‐acetylphenylalanine, is the possibility of it being cleaved from the peptide and becoming incorporated into endogenous proteins. To determine whether this occurs, an in vitro experiment to assess the cell viability and amino acid incorporation into endogenous proteins using primary male rat hepatocytes in the presence of [ 14 C]4‐acetylphenylalanine, 4 or [ 14 C(U)]L‐phenylalanine was conducted. [ 14 C]4‐acetylphenylalanine, 4 was prepared in 2 radiochemical steps from [1‐ 14 C]acetyl chloride in an overall 8% radiochemical yield and in 99.9% radiochemical purity. The results showed that there was no evidence of carbon‐14 incorporation into hepatocyte endogenous proteins with [ 14 C]pAcF and there was no difference between it and L‐phenylalanine in cell viability assessments at any of the concentrations studied between 0.1 and 1000 μM. Abstract : [ 14 C]4‐Acetylphenylalanine ([ 14 C]pAcF) was synthesized in 8% yield from [1‐ 14 C]acetyl chloride and the amine protected ethyl ester of phenylalanine. It was prepared for use in a cell viability study and to determine whether it could be incorporated into endogenous proteins using primary male rat hepatocytes.The results showed that there was no evidence of carbon‐14 incorporation into hepatocyte endogenous proteins and there was no difference between it and L‑phenylalanine in cell viability assessments.